Micropropagation of sweet pepper (Capsicum annuum var. Najera) and habanero pepper (Capsicum chinense Jacq) with the aim to genetic improvement of the culture - Cetz Iuit, Jorge (2005)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2005